MODEL PENGEMBANGAN USAHA SERABUTAN BERBASIS SUMBER INFORMASI KEPUSTAKAAN DI DESA - Pawit M. Yusup (Perpustakaan Nasional RI, 2016)
Rural poverty is known as a condition of a group of people associated with the economic and non-economic aspects such as social, cultural, health, education, psychology, environment, law, anthropology, as well as personal aspects of the poor themselves, including the needs and types of livelihood. This research attempted to comprehensively recognise the types of livelihoods information sought and used by poor people in rural areas, which are generally casual and has been used as their survivability base. It is then linked to the main aspects of their basic needs and mapped according to each characteristics. Method used was mentoring or Participatory Research Appraisal (PRA) as an implementation-based effort of the results of reading literature about enterpresneurship provided by libraries in villages. The research described a model for developing casual business that can be implemented for poor people in villages. One of the outputs was the formulation of casual business development model which was based on the usability of various literature information sources in villages.